Hibriditas dan Ambivalensi pada Novel Kokoro Karya Natsume Souseki: Teori Poskolonial Homi K. Bhabha - Foni Pramesti; Anas Ahmadi; Moh. Ahsan Shohifur Rizal (Indo Publishing, 2026)
This study aims to identify and analyze the forms of hybridity in the Kokoro by Natsume Souseki using Homi K. Bhabha’s postcolonial theory. The research employs a qualitative method with an interpretative approach, supported by Gadamer’s hermeneutic analysis to explore meanings within the text. The data consist of narrative and dialogue excerpts that reflect the dynamics of identity, which are analyzed based on three indicators of hybridity: partial presence, ambivalence of identity, and in-between space. The findings reveal that the characters experience identity struggles due to the encounter between traditional Japanese values and Western modernity during the Meiji era. These forms of hybridity demonstrate that the characters’ identities are unstable, fragmented, and continuously negotiated. In conclusion, the novel represents identity as a dynamic construction shaped through cultural interaction. This study highlights the significance of hybridity theory in translation studies and postcolonial literary analysis, and it suggests further research comparing the original and translated texts to deepen the understanding of identity transformation across cultural contexts.